Interpreting classical arts in postmodern advertising from the perspective of intertextuality - Elizabeth Susanti; Miky Endro Santoso (Universitas Indraprasta PGRI, 2025)
Artwork and advertising design differ in how they convey information. Art is created for its own sake, while advertising design aims to deliver persuasive messages to sell a product. Although art and advertising communicate differently, many advertisements use classical artworks to convey product meanings. The transformation of classical art as a reference for advertising reflects the phenomenon of postmodernism. By studying the characteristics of postmodernism, such as information construction and aesthetic meaning, this research explains how advertising phenomena are produced and what messages classical art can communicate through advertising. This study employed a qualitative case study approach combined with visual semiotic analysis, to examine selected advertisements that reinterpret classical artworks. Each case was analyzed to identify the processes of deconstruction and reconstruction using pastiche and parody and to interpret the intertextual meanings generated within advertising messages. The findings show that classical art is visually reconstructed in postmodern advertising to create cultural and symbolic value. Pastiche tends to strengthen luxurious and high-class brand identities by evoking artistic prestige, while parody provides humorous reinterpretations that engage broader audiences. The research concludes that intertextuality functions as a visual bridge between classical art and contemporary advertising communication, providing new ideas for creative design strategies. This study contributes to the field of visual communication design by demonstrating how classical aesthetics can be transformed into persuasive imagery in postmodern advertising.